Briefing a practical guide to Riba Plan of work 2013 stages 7, 0 and 1 - Fletcher, Paul; Satchwell, Hilary (RIBA stage guides, 2015)
This is the first in a must-have series of step-by-step guides to using the new RIBA Plan of Work 2013 on your project. Drawing together Stages 7, 0 and 1 this book is about much more than briefing; it guides you through the brand new Stage 0 - Strategic Definition - as well as how Stage 7 - In Use - can feed into the definition process reflecting the circular principles of the new Plan of Work. Providing a practical tool to running an efficient project each guide follows the same format leading you through the core tasks at each stage supported by tips, definitions, templates and useful techniques. Five theoretical scenarios are used throughout the guides to illustrate how the Plan of Work can be applied on various project types and sizes including an extension to a house, a new library and a large office building. These guides will provide unrivalled support for practices on all projects - large and small - and across all types of procurement